Effects of hyperoxia during recovery from 5×30-s bouts of maximal-intensity exercise - Sperlich, B.; Zinner, C.; Krueger, M.; Wegrzyk, J.; Achtzehn, S.; Holmberg, H. C. (Journal of Sports Sciences, 2012)
We test the hypothesis that breathing oxygen-enriched air (FIO2 = 100%) maintains exercise performance and reduces fatigue during intervals of maximal-intensity cycling. Ten well-trained male cyclists (age 25 ± 3 years; peak oxygen uptake 64.8 ± 6.2 ml/kg·min; mean ± s) were exposed to either hyperoxic or normoxic air during the 6-min intervals between five 30-s sessions of cycling at maximal intensity. The concentrations of lactate and hydrogen ions [H+], pH, base excess, oxygen partial pressure, and oxygen saturation in the blood were assessed before and after these sprints. The peak (P = 0.62) and mean power outputs (P = 0.83) with hyperoxic and normoxic air did not differ. The partial pressure of oxygen was 4.2-fold higher after inhaling hyperoxic air, whereas lactate concentration, pH, [H+], and base excess (P = 0.17) were not influenced. Perceived exertion towards the end of the 6-min periods after the fourth and fifth sprints (P < 0.05) was lower with hyperoxia than normoxia (P < 0.05). These findings demonstrate that the peak and mean power outputs of athletes performing intervals of maximal-intensity cycling are not improved by inhalation of oxygen-enriched air during recovery.